An Emperical Evidence on Customers’ Perception of Bank Services’ Quality in Cameroon - Fabien, Sundjo; Kevin, Fongang Singhe; Kum, Fuein Vera (International Journal of Economics and Financial Modelling, 2020)
This study purport to investigate the perception of service delivery quality from banks customers in Cameroon. Specifically, the study examined customers’ perception of service quality dimensions (tangibility, reliability, competence, and convenience) within some selected banks. In order to achieve these objectives a sample of 500 bank customers were chosen from the Littoral and South West Region by making use of a mixture of cluster, stratified, simple random and convenient sampling techniques. Data was collected with the help of a well-structured questionnaire, the resultant data were subsequently analyzed using descriptive statistics, Independent T-test and One-way analysis of variance (ANOVA). The results among others indicated that the perception of bank services’ quality by customers was positive for the tangibility, reliability and convenience dimensions but negative for the competence dimension. In addition, it was found that customers of Afriland First Bank, SGBC, BICEC, ECOBANK, UBA, Citi Bank and SCB had a more positive perception of bank services’ quality in terms of tangibility and reliability than customers in CBC, UBC, NFCB and Atlantic Bank. Further, age and monthly income level greatly influence customer’s perception of service quality, meanwhile gender had no significant influence on customers’ perception of service quality. Policy-wise, banks should ameliorate on the competence dimension by making in-service training and refresher courses for employees. They should equally make banking more convenient for female customers, use age as a strategic tool and should train their employees effectively if they must succeed in this era of stiff competition.